Effects of Ageing on the Color and Surface Chemistry of Paulownia Wood (P. elongata) from Fast Growing Crops - LIU Xin You; TIMAR Maria Cristina; VARODI Anca Maria; SONG Lin Yi (BioResources, 2016)
The behavior of paulownia wood (Paulownia elongata) was investigated using three different ageing tests: simulated natural ageing under the influence of light under indoor conditions, temperature-induced ageing in the dark, and UV-induced ageing. Ageing effects were evaluated by color measurements in the CIE Lab system. Simulated natural ageing of wood in indoor conditions (6 months) and UV-accelerated ageing (72 h) are complex and dynamic processes, which resulted mostly in yellowing of the samples due to photo-degradation. Temperature-induced ageing (288 h at 100 C) resulted mostly in a rapid and visible darkening of the paulownia wood. Comparative in-time evolution of color changes during accelerated UV ageing testing and simulated natural ageing testing under indoor conditions allowed the estimation of an acceleration index of about 50X. Fourier transform infrared spectroscopy (FTIR) was used to examine specific chemistry changes occurring during these ageing tests. UV light from natural or artificial sources caused primarily lignin degradation followed by oxidative processes leading to carbonyl-containing chromophores. Temperature-induced partial degradation of hemicelluloses and oxidative processes resulted in the formation of chromophores containing mostly conjugated carbonyl groups. This research highlighted that paulownia wood (P. elongata) is quite sensitive to ageing under the action of light and temperature, which cause notable color and surface chemistry changes.
Keywords: Paulownia; Artificial ageing; Natural ageing; Color change; FTIR